Trajetórias e interações: os objetos da caixa didática “Padrões de Beleza” do Museu de Arqueologia e Etnologia da Universidade Federal do Paraná (MAE-UFPR) - Vörös, Aline da Silva Araújo (2015)
The main purpose of this research is to explore a collection of objects which compose a material named “caixa didática Padrões de Beleza”, created by a group responsible for Educational Actions in the “Museu de Arqueologia e Etnologia da Universidade Federal do Paraná (MAE-UFPR)”. This research focuses in the making process of this material, seeking, in particular, the understanding of the relations and interactions developed between the agents in charge and those museological objects chosen by them to be part of this “Caixa”. The analysis is based essentially on material culture studies and anthropology of objects. This research comprises the construction of an inventory of the objects, ethnographic research and the mapping of the information gathered, concluding with the writing of the dissertation.